ANALISIS TERJADINYA KERETAKAN CYLINDER HEAD MESIN PENGGERAK UTAMA DI KAPAL MT GIAT ARMADA 01 - Trisya Ristanto; Suhendra Afriandi; Yeyen Herlina (ADISAM PUBLISHER, 2026)
The cylinder head is a vital component of the ship's main propulsion engine, functioning to close the cylinder block and form the combustion chamber. Cracking in the cylinder head can cause fatal ship operational disruptions. This study aims to analyze the causes of cylinder head cracking in the main propulsion engine on MT Giat Armada 01 and determine preventive measures. The research method used is qualitative descriptive based on direct observation, interviews, and literature review. The results show that cylinder head cracking is caused by three main factors: (1) material fatigue due to exceeding the factory-specified working hours limit of 6,000 hours, (2) insufficient cooling of the cylinder head causing overheating, and (3) secondary combustion (detonation) causing carbon deposit accumulation. Recommended preventive measures include replacing the cylinder head according to the maintenance schedule, routine cooling system inspections, and periodic maintenance of the fuel system and injectors.